Synthesis and biological evaluation of novel 2-phenylquinazoline-4-amine derivatives: identification of 6-phenyl-8H-benzo[g]quinazolino[4, 3-b]quinazolin-8-one as a highly potent inducer of NAD(P)H quinone oxidoreductase 1. (1st November 2016) - Ghorab, Mostafa M.; Alsaid, Mansour S.; El-Gazzar, Marwa G.; Higgins, Maureen; Dinkova-Kostova, Albena T.; Shahat, Abdelaaty A.
Abstract: A novel series of quinazoline compounds (2 –14 ) incorporating biologically active heterocyclic moieties were designed and synthesized. The structure of the newly synthesized compounds was recognized on the basis of elemental analyses, IR, 1 H-NMR, 13 C-NMR and mass spectral data. All compounds were evaluated for their ability to induce the cytoprotective enzyme NAD(P)H:quinone oxidoreductase 1 (NQO1) using a quantitative bioassay and a docking study was performed in the Kelch domain of Keap1 obtained from the Protein Data Bank (PDB ID: 4IQK) to explore the ability of the synthesized compounds to block the Nrf2-binding site of Keap1. All of the synthesized compounds showed concentration-dependent inducer activity with potencies in the low- or sub-micromolar range. Compound12 was the most potent inducer in this new series, with a concentration that doubles the specific activity of NQO1 (CD value) of 70 nM. The identification of this compound offers a new chemical scaffold for future development of highly potent inducers.